Memory Field - Sophonkunkit, Ladapha (Taideyliopiston Teatterikorkeakoulu, 2023)
This written component of the MA thesis addresses self-censorship that derives collective trauma that has been silenced. It enters through the memory of the 6 October Massacre at Thammasart University in 1976. Referring to Thongchai Winichakul, a historian and researcher who was also a victim of the traumatic incident, and who coined the term 'unforgetting'. He highlighted that memories of political atrocities can lead to a memory impasse in society. It examines the condition of unforgetting within the symptom of silencing that has persisted among the Thai people for generations. The thesis also explores self-censorship during the artistic process and how collaborative and participatory methods help to overcome this issue in making of the artistic work, the memory field performance. Additionally, I have also incorporated the concept of memory field by anthropologist Daniel T. Linger to help me examine the interweaving of my personal and social memories within the framework of this thesis together with the notions of recollecting and recalling that resonate with my artistic approach. A close examination of and inspiration from Doris Salcedo's work "Noviembre 6 y 7" (2002) in dialogue with Mieke Bal's analysis in the book, Of what one cannot speak: Doris Salcedo's Political Art, has shaped my thinking and artistic approach. In the section on collective action, I discuss how to engage participants using memories and reflect on the tools and approaches I have developed throughout my research. Ultimately, I explore and explain how I design collaborative processes to address and overcome the issue of self-censorship that I have encountered.
Keywords: performanssi; LAPS